Synthesis, characterization and antitumor activity of novel tetrapodal 1, 4-dihydropyridines: p53 induction, cell cycle arrest and low damage effect on normal cells induced by genotoxic factor H2O2. Issue 47 (25th April 2016) - Mohamed, Magda F.; Darweesh, Ahmed F.; Elwahy, Ahmed H. M.; Abdelhamid, Ismail A.
Abstract : Synthesis of novel tetrakis(2, 6-dimethyl-4-phenyl-1, 4-dihydropyridinyl)methanes5a–d by acid-catalyzed condensation of the tetrakis-aldehydes6a–d with eight equivalents of 3-aminobut-2-enenitrile2 is reported. Antitumor activities of compounds5a–d were also investigated. Abstract : Synthesis of novel tetrakis(2, 6-dimethyl-4-phenyl-1, 4-dihydropyridinyl)methanes5a–d by acid-catalyzed condensation of the tetrakis-aldehydes6a–d with eight equivalents of 3-aminobut-2-enenitrile2 is reported. The structures of5a–d are confirmed by different spectral tools. In vitro, cytotoxic screening assay for novel tetrapodal 1, 4-dihydropyridines (5a–d ) was performed on five different human cell lines (HCT116, A549, MCF7, PC3, and HEPG2). The compounds showed higher cytotoxic activity against (A549, HCT116, and MCF7) cell lines. The loss of the cytotoxic activity was observed in the case of PC3 and HEPG2 cell lines. Compound5b showed the highest cytotoxic activity against the three lines (A549, HCT116, and MCF7). In an attempt to know the mechanism followed by the compounds to inhibit cell proliferation, compound5b was chosen for molecular studies. Compound5b induced apoptotic inhibition of the proliferation of human colon adenocarcinoma HCT116 cells through induction of the tumor suppressor protein p53, BAX, and through the inhibition of anti-apoptotic proteins by decreasing BCL2 gene expression using real-time PCR. Regarding cell cycle analysis, compound5b induced G1 arrest against the three lines (MCF7, HCT116, and A549). Compound5b has been found to reduce apoptosis of human normal melanocytes HFB4 and normal fibroblasts BHK that has been treated with genotoxic factor H2 O2 . Moreover, compound5b has a potent protective effect against DNA damage, as indicated by the in vitro studying of different concentrations of5b against two different types of healthy DNA (calf-thymus DNA and pBR322 DNA).